Phytochemical composition and bioactive compounds of common purslane (Portulaca oleracea L.) as affected by crop management practices. (September 2016) - Petropoulos, Spyridon; Karkanis, Anestis; Martins, Natalia; Ferreira, Isabel C.F.R.
Abstract: Background: Recently, there is an increasing market trend for innovative functional/power foods and dietary supplements from natural compounds. Therefore the evaluation of potential species that could be used for that purpose is of major importance. Common purslane is such a species due to its high nutritional value, since it is considered the richest plant source in omega-3 fatty acids (especially α-linolenic acid). Scope and approach: In this review all the aspects related with chemical composition and health effects of common purslane are presented. Additionally, an overview of cultivation practices and breeding prospects and their effect on quality are also presented. Special interest is given on bioactive compounds such as α-linolenic acid and oxalic acid due to their important effects on human health. Key findings and conclusions: Purslane has been used in human diet throughout the centuries, however there are health concerns regarding its oxalic acid content that limit the recommendation of its regular use in human diet. Cultivation practices and breeding selection have been confirmed to allow for managing the content of the main bioactive compounds and consequently increase the added value of the final product. However, further studies are need in order to incorporate purslane in food industry, either as raw, minimally processed and processed food product, or as an ingredient in food and dietary supplements and drugs. In conclusion, the high nutritional and therapeutic value of common purslane should be further capitalized, whereas the application of proper cultivation practices could contribute to this purpose by improving quality. Highlights: Purslane is the richest plant source in α-linolenic acid. Nitrogen source and nitrogen rate can affect α-linolenic and oxalic acid content. Oxalic acid content can be manipulated through breeding and cultivation practices. Late harvest is beneficial for quality (α-linolenic acid and oxalates content). Purslane has a great potential as a functional or power food.